Pembelajaran Biologi Pokok Bahasan Sistem Pernapasan pada Manusia melalui Media Gambar di MTsN Jongar Kabupaten Aceh Tenggara - Safryadi A (Universitas Islam Negeri Ar-Raniry, 2016)
This study aims to find out the students’ mastery learning outcomes in learning biology on the concept of human respiratory system by using images media in MTsN Jongar Aceh Tenggara Regency. The method used was Quasi Experimental Research with one group pretest-posttest design. The samples of this research were students class VIII/A of MTsN Jongar Aceh Tenggara Regency. The data were collected by using test, namely pre-test and post-test. They were analyzed by using descriptive quantitative technique. The results showed that students’ mastery learning outcpme classically was 89,47% with the criteria of minimum passing grade was 75. It can be concluded that media images could increase the students’ mastery in learning biology on the concept of human respiratory system at MTsN Jongar Aceh Tenggara Regency.